Prestasi alam sekitar rantaian industri tekstil dan pakaian di Malaysia: Faktor dorongan daripada perspektif pemodenan ekologi - Er Ah Choy (Faculty of Social Sciences and Humanities, UKM,Bangi, 2009)
The textile and apparel industry has come to be regarded as a sunset industry especially with the membership of China in the World Trade Organisation and the stiff competition ensuing from an environment of unrestricted quota since early 2005. The highly keen competition from the Chinese manufacturers in the form of lowered production costs had, furthermore, impacted adversely on the environmental performance of the industry. Yet, in Malaysia the textile-apparel lingkage had managed to register a 90 percent compliance with the country‘s 1978 Environmental Quality Act (Clean Air). This paper embarks on a quantitative test of the Malaysian textile-apparel industrial lingkage within the paradigm of the ecological modernisation theory ( EMT). Results of the Kendall tau-b statistical tests establish the role of three factors in driving positive ecological performance of the textile-apparel industrial lingkage, namely, the exposure to international trade, the level of vertical integration, and the intensity of international relation. The paper concludes that the application of EMT needs to be modified and adapted to the Malaysian local as well as institutional contexts to enhance further the already positive contribution of the existing environmental certification to environmental harmonisation practices that are characteristic of the EMT